Crowdsourced Evaluation of Robot Programming Environments: Methodology and Application - Daria Piacun (MDPI AG, 2021)
Industrial robot programming tools increasingly rely on graphical interfaces, which aim at rendering the programming task more accessible to a wide variety of users. The usability of such tools is currently being evaluated in controlled environments, such as laboratories or companies, in which a group of participants is asked to carry out several tasks using the tool and then fill out a standardized questionnaire. In this context, this paper proposes and evaluates an alternative evaluation methodology, which leverages online crowdsourcing platforms to produce the same results as face-to-face evaluations. We applied the proposed framework in the evaluation of a web-based industrial robot programming tool called Assembly. Our results suggest that crowdsourcing facilitates a cost-effective, result-oriented, and reusable methodology for performing user studies anonymously and online.